2018
DOI: 10.1080/09273948.2018.1433303
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Positive Findings ofToxoplasma gondii-Specific Immunoglobulin M Serum Antibody in Uveitis Patients to Confirm Ocular Toxoplasmosis

Abstract: The T. gondii IgM serum Ab is a specific biomarker for diagnosis of primary OT. Epidemiological studies are warranted to investigate the non-classic transmission routes of T. gondii in OT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
2
3
0
2
Order By: Relevance
“…In our population, the IgG value in patients with ocular toxoplasmosis was about nine-fold higher than in patients not diagnosed with ocular toxoplasmosis (3953 IU/ml vs 428 IU/ml, respectively). This result is in accordance with previous studies in South Korea (Park et al) [ 39 ] and Switzerland (Papadia et al) [ 40 ] populations; nonetheless, the IgG value in our study is found to be much higher than those two previous reports. In Park et al study, they found that the average toxoplasma IgM and IgG titers were 2.29 IU/mL and 223.4 IU/mL, respectively [ 39 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our population, the IgG value in patients with ocular toxoplasmosis was about nine-fold higher than in patients not diagnosed with ocular toxoplasmosis (3953 IU/ml vs 428 IU/ml, respectively). This result is in accordance with previous studies in South Korea (Park et al) [ 39 ] and Switzerland (Papadia et al) [ 40 ] populations; nonetheless, the IgG value in our study is found to be much higher than those two previous reports. In Park et al study, they found that the average toxoplasma IgM and IgG titers were 2.29 IU/mL and 223.4 IU/mL, respectively [ 39 ].…”
Section: Discussionsupporting
confidence: 94%
“…This result is in accordance with previous studies in South Korea (Park et al) [ 39 ] and Switzerland (Papadia et al) [ 40 ] populations; nonetheless, the IgG value in our study is found to be much higher than those two previous reports. In Park et al study, they found that the average toxoplasma IgM and IgG titers were 2.29 IU/mL and 223.4 IU/mL, respectively [ 39 ]. We presumed that different populations in different geographic areas might be attributed to this phenomenon.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…mehrerer fokaler nekrotisierender Netzhautläsionen -typischerweise in der Nähe einer vorbestehenden chorioretinalen Narbe -erreicht eine diagnostische Spezifität von etwa 93 %. Fehlen diese Narben, wird nach SUN der Erregernachweis mittels Polymerasekettenreakti- [11]. Der Nachweis von Toxoplasma-IgG bestätigt die Durchseuchung, aber weder das Vorhandensein von Antikörpern noch die Titerhöhe sind ausreichend spezifisch, um etwas über die Rolle der Toxoplasmose bei einer aktiven Uveitis auszusagen [14].…”
Section: » Der Klinische Befund Wird Als Wichtigstes Diagnostisches K...unclassified
“…[9,10] Similar to most infections, the first antibodies to appear against Toxoplasma are Immunoglobulin M (IgM), usually within the first week following infection. IgM levels rise until their peak at 1-3 months, [11] then slowly decrease over the following 6 months, generally becoming undetectable after 6-9 months. However, IgM may remain detectable by Elisa linked immunosorbent assay (EIA) for up to 18 months.…”
Section: Introductionmentioning
confidence: 99%